2012
DOI: 10.1111/jasp.12069
|View full text |Cite
|
Sign up to set email alerts
|

How “American” is Barack Obama? The Role of National Identity in a Historic Bid for the White House

Abstract: Against the backdrop of the 2008 presidential election, we examined the extent to which the American identity was implicitly and explicitly associated with Barack Obama compared to Tony Blair (Study 1), Hillary Clinton (Study 2), and John McCain (Studies 3 and 4). When conscious control was relatively limited and targets were categorized based on race, the American identity was less strongly associated with Obama than with the other candidates. This effect was stronger than when the candidates were categorized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…Recent evidence from psychology provides some reason to expect that anti-Black attitudes may be more directly associated with perceptions that President Obama is un-American. In particular, many White Americans appear to view Whiteness as central to American identity (Devos and Banaji, 2005;Devos and Ma, 2012), and this schema appears to be predominant among those who hold negative views of nonWhites (Yogeeswaran and Dasgupta, 2010). Individuals associating Whiteness and American identify might therefore be more prone to accepting a foreign birthplace for Mr. Obama when confronted with circulating claims that he was born in Kenya or perhaps elsewhere.…”
Section: Discussionmentioning
confidence: 82%
“…Recent evidence from psychology provides some reason to expect that anti-Black attitudes may be more directly associated with perceptions that President Obama is un-American. In particular, many White Americans appear to view Whiteness as central to American identity (Devos and Banaji, 2005;Devos and Ma, 2012), and this schema appears to be predominant among those who hold negative views of nonWhites (Yogeeswaran and Dasgupta, 2010). Individuals associating Whiteness and American identify might therefore be more prone to accepting a foreign birthplace for Mr. Obama when confronted with circulating claims that he was born in Kenya or perhaps elsewhere.…”
Section: Discussionmentioning
confidence: 82%
“…Across several studies, data revealed that the extent to which Obama was implicitly perceived to be American (relative to Clinton, McCain, and Blair) predicted increased willingness to vote for him and donate to his campaign. Similarly, the extent to which Obama was explicitly perceived to be American relative to others predicted greater willingness to vote for Obama and donate to his campaign (Devos & Ma, 2013).…”
Section: How Do Varying Conceptions Of Nationality Influence Attitudementioning
confidence: 99%
“…In particular, we manipulated the labels used to categorize the candidates by either asking participants to categorize stimuli based on personal identity labels (“Barack Obama” and “Mitt Romney”) or racial identity labels (“Black” and “White”). This manipulation has been shown to effectively focus participants’ attention on specific aspects of a target's identity (Devos & Ma, , ; Mitchell, Nosek, & Banaji, ). In line with previous research, we predicted that the tendency to view Obama as more American than Romney and like Obama more than Romney when the focus is on the candidates’ personal identities (see Study 1) would be reduced when the candidates’ racial identities were made salient .…”
Section: Studymentioning
confidence: 99%